The Consequences of COVID-19 Toward Human Growth: The Role of Traumatic Event and Coping Strategies Among Indonesian Sample - Kaloeti, Dian Veronika Sakti; Ardhiani, Lusi Nur; Stück, Marcus (Frontiers in Psychology, 2021)
COVID-19 has brought a massive psychological impact on individuals' life. The current study sets a significant purpose to test the model whether post-traumatic stress and coping strategies affect stress-related growth regarding the COVID-19 event. One hundred and ninety-nine participants have participated in an online survey in the period of lockdown. The proposed hypotheses model is further tested using PLS-SEM. The first model explains a significant moderate, 46% amount of variance for stress-related growth. With gender as moderator, the second model explains a significant 29% amount of variance for stress-related growth, which is also moderate. This study shows that active coping strategies and positive affirmation significantly influence individual stress-related growth. The trauma event (COVID-19) does not significantly affect growth. Women experience trauma compared to men, besides active coping with the COVID-19 situation is higher in men than women. Using the Bio-centric perspective, having a positive connection through acceptance and awareness of the situation, self-care, and affective interaction with others would develop growth regarding traumatic situations. Further, interventions about coping skills and positive affirmations are essential to give, especially to vulnerable groups such as women.